2014
DOI: 10.2147/ijn.s57935
|View full text |Cite
|
Sign up to set email alerts
|

Immunotoxicity of zinc oxide nanoparticles with different size and electrostatic charge

Abstract: While zinc oxide (ZnO) nanoparticles (NPs) have been recognized to have promising applications in biomedicine, their immunotoxicity has been inconsistent and even contradictory. To address this issue, we investigated whether ZnO NPs with different size (20 or 100 nm) and electrostatic charge (positive or negative) would cause immunotoxicity in vitro and in vivo, and explored their underlying molecular mechanism. Using Raw 264.7 cell line, we examined the immunotoxicity mechanism of ZnO NPs as cell viability. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…It was believed that the positively charged NPs induce more toxicity and it can affect the cellular uptake and intracellular location (Asati et al, 2010;De Angelis et al, 2013). Kim et al (2014) also proved the higher cytotoxicity of positively charged ZnO NPs in comparison to the negatively charged ones. In addition, genotoxicity and DNA damage was seen in ZnO treated MRC5 lung cells along with the high secretion of extracellular LDH and reduction in cell viability (Ng et al, 2017).…”
Section: Zinc and Zinc Oxide Cytotoxicitymentioning
confidence: 95%
See 1 more Smart Citation
“…It was believed that the positively charged NPs induce more toxicity and it can affect the cellular uptake and intracellular location (Asati et al, 2010;De Angelis et al, 2013). Kim et al (2014) also proved the higher cytotoxicity of positively charged ZnO NPs in comparison to the negatively charged ones. In addition, genotoxicity and DNA damage was seen in ZnO treated MRC5 lung cells along with the high secretion of extracellular LDH and reduction in cell viability (Ng et al, 2017).…”
Section: Zinc and Zinc Oxide Cytotoxicitymentioning
confidence: 95%
“… Thevenot et al (2008) demonstrated that negative charged COOH treated TiO 2 NPs had not an impact on the cell viability because they can easily be absorbed into the cells without any membrane binding. In fact, the positively charged particles are more toxic and the variance surface charge determines the cellular uptake, the positively charged ZnO NPs show increased toxicity values compared to negatively charged NPs ( Kim et al, 2014 ).…”
Section: Physicochemical Properties Of Nanoparticlesmentioning
confidence: 99%
“…It has been reported that Nano-ZnO differed from ordinary ZnO due to its unique chemical and physical properties, including the effect of volume, surface, quantum size and macro quantum tunnel [ 5 ], in addition, Nano-ZnO only partly dissolved in gastric fluid in vivo [ 6 ], and showed a limited solubility in neutral environments [ 7 ]. Thus, Nano-ZnO is likely absorbed as the intact particulate form and as zinc ions [ 8 ]. Studies about Nano-ZnO application mainly focused on the hazards or toxicity in a dose- and time-dependent manner, which was probably caused by reactive oxygen species, oxidant injury or excitation of inflammation [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, CQ-induced pruritus is also mediated by increased production of NO (linked to cGMP) 41. In in vivo studies, ZnO NPs have been reported to reduce NO level 36,41. Here, the reduction in scratching intensity could be attributed to the ZnO NPs’ NO lowering property.…”
Section: Discussionmentioning
confidence: 93%
“…ZnO NPs have successfully been synthesized using various plant extracts as reducing agents 35. Yet, toxicities and bio-hazards of ZnO NPs are conflicting 36…”
Section: Introductionmentioning
confidence: 99%